Peru - Country Note on Climate Change Aspects in Agriculture - World Bank (Washington, DC, 2012)
This country note briefly summarizes information relevant to both climate change and agriculture in Peru, with focus on policy developments (including action plans and programs) and institutional make-up. Like most developing countries, Peru has submitted only one national communication to the United Nations Framework Convention on Climate Change (UNFCCC), with the second one under preparation. Land use change and forestry are the largest contributors to greenhouse gas (GHG) emissions in the country. The emission reduction potential of the agricultural (including land use change and forestry) sector is large, though not yet sufficiently explored. Peru currently counts with one Clean Development Mechanism (CDM) project in the agricultural sector, and one CDM reforestation project. Reducing vulnerability to climate change and, in particular, to water scarcity due to variations in precipitation and glacier retreats is of increasing importance in the agricultural sector, coupled with more sustainable land management practices.